Capture and Transfer of Simian Immunodeficiency Virus by Macaque Dendritic Cells Is Enhanced by DC-SIGN - Yu Kimata, Monica T. (American Society for Microbiology, 2002)
Dendritic cells (DCs) are among the first cells encountered by human and simian immunodeficiency virus (HIV and SIV) following mucosal infection. Because these cells efficiently capture and transmit virus to T cells, they may play a major role in mediating HIV and SIV infection. Recently, a C-type lectin protein present on DCs, DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN), was shown to efficiently bind and present HIV and SIV to CD4(+), coreceptor-positive cells in trans. However, the significance of DC-SIGN for virus transmission and pathogenesis in vivo remains unclear. Because SIV infection of macaques may represent the best model to study the importance of DC-SIGN in HIV infection, we cloned and characterized pig-tailed macaque DC-SIGN and generated monoclonal antibodies (MAbs) against it. We demonstrate that, like human DC-SIGN, pig-tailed macaque DC-SIGN (ptDC-SIGN) is expressed on DCs and macrophages but not on monocytes, T cells, or B cells. Moderate levels of ptDC-SIGN expression were detected on the surface of DCs, and low-level expression was found on macrophages. Additionally, we show that ptDC-SIGN efficiently binds and transmits replication-competent SIVmne variants to CD4(+), coreceptor-positive cells. Moreover, transmission of virus between pig-tailed macaque DCs and CD4(+) T cells is largely ptDC-SIGN dependent. Interestingly, MAbs directed against ptDC-SIGN vary in the capacity to block transmission of different SIVmne variants. These data demonstrate that ptDC-SIGN plays a central role in transmitting virus from macaque DCs to T cells, and they suggest that SIVmne variants may differ in their interactions with ptDC-SIGN. Thus, SIVmne infection of pig-tailed macaques may provide an opportunity to investigate the significance of DC-SIGN in primate lentiviral infections.